The Role of Behavioral and Cognitive Cultural Orientation on Mexican American College Students' Life Satisfaction. (January 2014) - Ojeda, Lizette; Edwards, Lisa M.; Hardin, Erin E.; Piña-Watson, Brandy
We examined the role of behavioral (acculturation and enculturation) and cognitive cultural orientation (independent and interdependent self-construal) on Mexican American college students' life satisfaction. Analyses explained 28% of the variance in life satisfaction, with social class, grade point average, and independent self-construal being unique predictors. Furthermore, enculturation was associated with increasing life satisfaction among those low in interdependent self-construal, whereas acculturation was associated with decreasing life satisfaction among those high in independent self-construal. Implications and directions for future research are discussed.